Epistemic Orientation Short Scale:: Development and Validity Evidence in a Sample of Psychotherapists - Palma, Emanuel Missias Silva; Gondim, Sônia Maria Guedes; Aguiar, Carolina Villa Nova (Paidéia (Ribeirão Preto), 2018)
Epistemic orientation refers to the preferred mode of accessing and using knowledge and is a construct of growing interest in psychotherapy research. In this context, the main objective of this study was to develop and provide initial validity evidence for a brief measure of epistemic orientation in a sample of Brazilian psychotherapists. Participants were 674 Brazilian psychotherapists (78.5% female), aged between 22 and 78 years. Exploratory and confirmatory factor analyses were conducted on different subsamples to establish the structure of the measure. Results revealed an instrument consisting of three factors (Rationalism, Intuitionism, and Empiricism) with good psychometric properties and fit indices (X2 = 1.92, GFI = 0.94, CFI = 0.95 and RMSEA = 0.06). Factors exhibited good internal consistency and convergent and discriminant validity. Criterion validity was evaluated by examining the scale’s ability to detect differences in the epistemic orientation dimensions as a function of therapist’s theoretical approach. Overall, the scale proved to be a valid self-report measure for investigating personal epistemology.